1995
DOI: 10.1113/expphysiol.1995.sp003889
|View full text |Cite
|
Sign up to set email alerts
|

Ca(2+)‐activated Cl‐ and K+ channels and their modulation by endothelin‐1 in rat pulmonary arterial smooth muscle cells

Abstract: SUMMARYUsing the patch-clamp recording technique, we observed that endothelin-1 (ET-1; 0.8-16nM) enhanced a voltage-activated outward current ('out) and induced periodic oscillations of inward current in smooth muscle cells isolated from small pulmonary arteries (200-400 ,um in diameter). Anion substitution experiments revealed that the ET-1-induced inward current was carried by Clions. Application of bosentan (10 #m; an ETA and ETB receptor antagonist) and FR 139317(1-10 uM; a selective ETA receptor antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Previous studies have indicated that the activation of ET-1 receptors mobilizes intracellular Ca ϩϩ stores in nonerythroid cells, [35][36][37][38] but whether cytosolic Ca ϩϩ in red cells is affected by ET-1 is unknown. Other intracellular signaling mechanisms that mediate ET-1 actions include phospholipase C, diacylglycerol, and PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the activation of ET-1 receptors mobilizes intracellular Ca ϩϩ stores in nonerythroid cells, [35][36][37][38] but whether cytosolic Ca ϩϩ in red cells is affected by ET-1 is unknown. Other intracellular signaling mechanisms that mediate ET-1 actions include phospholipase C, diacylglycerol, and PKC.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the ability of a range of nucleotides to activate oscillatory inward currents, membrane current elicited over a 1-minute period was digitized at 100 Hz and integrated (pClamp software; version 6.2), as previously described, 25 giving a value in nA ⅐ ms. Contractions were normalized and expressed as N/mm 2 . Data are presented throughout as meanϮSEM.…”
Section: Discussionmentioning
confidence: 99%
“…Inward Cl − currents (due to Cl − efflux) are enhanced by α-adrenergic stimulation in rabbit portal vein myocytes (13), by endothelin-1 or angiotensin II in rat pulmonary artery myocytes (20,45,46), and by endothelin-1 or vasopressin in A7r5 cells (56). Furthermore, the stimulation of Cl − efflux has been implicated in the vasoconstrictor effects of endothelin-1 in rabbit basilar artery (10) and norepinephrine in rat resistance arteries (33) and aorta (32).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%